A simple and rapid approach to develop recombinant avian herpesvirus vectored vaccines using CRISPR/Cas9 system. Issue 5 (29th January 2018) - Tang, Na; Zhang, Yaoyao; Pedrera, Miriam; Chang, Pengxiang; Baigent, Susan; Moffat, Katy; Shen, Zhiqiang; Nair, Venugopal; Yao, Yongxiu
Highlights: Development of a rapid pipeline for generating recombinant HVT-based vaccines. NHEJ repair pathway makes targeted insertion of the foreign gene more efficient. Incorporation of RFP cassette enables the easy identification of recombinant virus. The recombinant virus has similar growth rate as parental virus with stable inserts. Abstract: Herpesvirus of turkeys (HVT) has been successfully used as live vaccine against Marek's disease (MD) worldwide for more than 40 years either alone or in combination with other serotypes. HVT is also widely used as a vector platform for generation of recombinant vaccines against a number of avian diseases such as infectious bursal disease (IBD), Newcastle disease (ND) and avian influenza (AI) using conventional recombination methods or recombineering tools on cloned viral genomes. In the present study, we describe the application of CRISPR/Cas9-based genome editing as a rapid and efficient method of generating HVT recombinants expressing VP2 protein of IBDV. This approach offers an efficient method to introduce other viral antigens into the HVT genome for rapid development of recombinant vaccines.